Strategi Digital Marketing Strategi Digital Marketing UMKM Jajanan Olahan Produk Pertanian di Kota Kendari - Halipa, Nur (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
UMKM snacks for agricultural products is a business unit that has great potential to continue to be developed at this time. So that the implementation of marketing strategies is very important to maintain business for MSME actors, processed snacks from Kendari City agricultural products. This study aims to analyze how the digital marketing strategy is implemented by MSME actors in processed agricultural products in the city of Kendari. Determination of respondents using a purposive sampling technique, the respondents who will be selected are MSME actors of processed agricultural products that have implemented digital marketing in their businesses. The results of the analysis show that MSME actors in Kendari city, especially processed agricultural products, actively use social media as a means of marketing their products, because using social media can have a significant positive effect on increasing turnover and profitability of MSME agricultural products.